Investigation of Separation Non-Persistent Faults in Fracture Mechanism of Rock Bridge - Nohekhan Hokmabadi, Nasim; Sarfarazi, Vahab; Moshrefifar, Mohamadreza (Civil Engineering Journal, 2016)
Rock mass is a heterogeneous material included joints, fractures and faults. The necessity of rock mechanics studies in conducting constructional issues has become important due to the increase in constructional works and the expansion of the structure’s dimension and especially creating underground spaces in rock masses. Faults are the most important discontinuous fractures in the earth's crust in which the two sides of the fracture have moved relative to each other. The purpose of this research is that if the non-persistent faults were situated adjacent to each other, how would be the shear failure mechanism of Rock Bridge surrounded between the faults. For this purpose, physical model consisting two horizontal edge faults and a surrounded angled fault was built; angularity of the central fault varies from 0° to 60° with increasing the 30°. The central fault places in 3 different positions. Along the lateral faults, 1.5 cm vertically far from the edge faults and 3 cm vertically far from the edge faults. All samples tested by uniaxial test machine so that shear load was distributed in the specimens due to special geometry of specimen. The results show that the failure pattern was mostly influenced by configuration of central joint, while the shear strength was linked to the failure pattern and failure mechanism.